1999
DOI: 10.2169/internalmedicine.38.632
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Selectin Families and Their Ligand Sialyl Lewis X in the Muscles of Inflammatory Myopathies. An Immunohistochemical Study.

Abstract: Object Adhesion molecules are suggested to play important roles in the pathogenesis of inflammatory diseases. Weexamined the expression of adhesion molecules in the muscles of human inflammatory myopathies. Methods Weimmunohistochemically studied the expression and distribution of two molecules in the selectin family (E-and P-selectin) and their commonligand sialyl Lewis X in 18 inflammatory myopathies, 13 disease controls, and 16 normal controls. Results In inflammatory myopathies, E-and P-selectin were upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
5
0
3
Order By: Relevance
“…The endothelial expressions of MECA-79 epitopes, sulfated extended core 1 lactosamine structures , 28 have been shown earlier to be induced during inflammation at the sites of acute transplant rejection, bronchial asthma, as well as inflamed muscle or skin lesions. 3,29,30 Here we expand these observations and show that endothelial mAb MECA-79 reactivity was present in many sites of inflammations, such as thyroiditis, psoriasis, ulcerative colitis, asthma, and organ transplant rejections.…”
Section: Discussionsupporting
confidence: 61%
“…The endothelial expressions of MECA-79 epitopes, sulfated extended core 1 lactosamine structures , 28 have been shown earlier to be induced during inflammation at the sites of acute transplant rejection, bronchial asthma, as well as inflamed muscle or skin lesions. 3,29,30 Here we expand these observations and show that endothelial mAb MECA-79 reactivity was present in many sites of inflammations, such as thyroiditis, psoriasis, ulcerative colitis, asthma, and organ transplant rejections.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to the recent theory described above, several mechanisms may be proposed and associated: 1) the blockade of IgG Fc receptors on phagocytic cells by the infused IVIG, thereby preventing the removal of cells, sensitized with autoantibodies of IgG isotype, from the circulation; 2) the presence of antiidiopathic antibodies capable of suppressing autoantibody secretion in the pool of plasma donors used for IVIG production; 3) a direct effect on B and T lymphocytes; 4) the inhibition of adhesion molecules and cytokine production; and/or 5) the presence of soluble CD4, CD8, and HLA in IVIG, which modify antigen recognition by target cells. These 2 last theories are probably important, since IVIG might also provide a source of antiidiotypic antibodies directed against chemokines, HLA antigens, adhesion molecules, and especially the selectin family, and antiapoptotic molecules and metalloproteases, which are known to be involved in the pathogenesis of myositis (22,(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of E-selectin in all endothelial cells in PM and DM was recorded by some authors 73 whereas others 28 observed it only in arterioles and venules. E-selectin expression was not recorded in most studies.…”
Section: Functional Roles Of Cytokines Cell Adhesion Molecules and mentioning
confidence: 92%
“…28,39,92 P-selectin expression was observed in endothelial cells, expression being stronger in PM than in DM, and in venules than in arterioles. 73 In keeping, SLe x , a common ligand for these selectins, was recorded in infiltrating leukocytes, interstitial tissues, and endothelial cells but also in some muscle fibers.…”
Section: Functional Roles Of Cytokines Cell Adhesion Molecules and mentioning
confidence: 94%